REPORTING ON SEXUAL VIOLENCE CASES AT THE SHIDDIQIYYAH ISLAMIC BOARDING SCHOOL IN JOMBANG ON KOMPAS.COM - Farida, Dewi Istiqomah; Munir, Ahmad (QAULAN: Journal of Islamic Communication, 2023)
Environment is currently of concern to the general public. One concerning case is what occurred at the Shidiqiyyah Islamic Boarding School, Jombang. This case has been widely reported by the media in Indonesia, including the online media Kompas.com, starting from the alleged case until it reached the stage of the sentencing hearing. This research examines five news stories from the online media Kompas.com regarding reporting on verdicts in cases of sexual violence at the Shiddiqiyyah Islamic boarding school, Jomban. The aim and formulation of the problem in this research is: How does the online media Kompas.com use framing structures (syntax, script, thematic, rhetorical). This research uses a qualitative approach by collecting data using non-participant observation and documentation. The data analysis technique uses Zhongdang Pan and Gerald M. Kosicki's framing analysis model with four structures: syntax, script, thematic, and rhetorical. The results of this research are (1). Syntactic Structure, Kompas.com media tries to show the events after the sentence was handed down to the perpetrator of sexual violence. (2). Kompas.com's media script structure tries to frame the facts and efforts of the victim while fighting for justice for the victim. (3). The thematic structure of the Kompas.com media shows that the verdict handed down did not match the victim's expectations. (4). Rhetorical structure, in Kompas.com media reporting, is seen using elements of the lexicon, this shows the emphasis in each news.